Tecnologia versus desempenho educacional: um estudo sobre a performance das escolas - Lima, José Vitor Cosme de (Universidade Federal Rural do Semi-Árido, 2017)
This study has as main objective to investigate the influence of technological tools on the performance of Brazilian schools. For this purpose, data from the Brazil Province - 90 years - were used for the period of 2013. The methodology used is called the effect treatment method and is based on the inference of counterfactual distributions. The main results indicate that technological factors have great importance in educational outcomes. However, heterogeneous results were observed according to region and point of distribution. Specifically, not the Northeast the contribution of the framework falls in half. For example, the effect of broadband internet access for Brazil is 3.4% in schools that have achieved an average performance against 1.7% for schools in the same situation.
Keywords: Tecnologia; desempenho nas escolas; IDC; technology; performance of school; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA